A Comparative Study of Ethical Perceptions of Managers and Non-Managers - Siu, Noel Y. M. (Journal of business ethics, 2009)
This study provides a comparison of the ethical perceptions of managers and non-managers, including professionals, teachers, sales persons and clerks, as well as technical and plant workers. Data of working individuals were collected in Hong Kong in the form of questionnaires which contain vignettes of questionable ethical issues. Factor analysis was used to identify the major ethical dimensions which were then used as the basis of comparison. Regression analyses were used to study the effect of various variables on ethical perceptions in terms of the identified dimensions. Our study reviews that managers tend to possess deontological views that are more ethical than that found in other occupations. The gap between managers and professionals in perceiving unethical behavior is narrower compared to that between the former and individuals in other occupations. The acceptability of unethical behavior tends to decline with income. Besides, there are indications that people working in non-profit organizations tend to have higher ethical standards. Based on our results, recommendations are made to improve the ethical culture of organizations.